INOVASI LAYANAN MANDIRI DI DESA BANA KECAMATAN BONTOCANI KABUPATEN BONE - Hajrah, Hajrah; Haerana, Haerana; Yahya, Muhammad (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the Self Service Innovation in Bana Village, Bontocani District, Bone Regency. The method used in this research is descriptive qualitative with 4 informants. This research information was collected through observation, interviews, and documentation. The results of this study can be seen from the aspect of relative adventage (plus value), which shows that service applications have more value when compared to the previous self-service applications that can be accessed online anytime and anywhere. From the compatibility aspect, it shows that the self-service application is in accordance with the needs of people who are far from the Bana Village office. From the aspect of complexity (complexity), it shows that self-service applications are often constrained by application errors and inadequate networks and people who lack understanding regarding the use of android mobile phones. From the aspect of observability (easy to observe), it shows that this self-service has a simple appearance so it is easy to use. Then from the triability aspect (can be tried), self-service is proven to be able to be tried, this can be seen from the number of letters that have been printed as many as 719 letters.